Chemical and Electrochemical Properties of Bamboo Activated Carbon Activate Using Potassium Hydroxide Assisted by Microwave-Ultrasonic Irradiation - Norakmalah Mohd Zawawi; Fazlena Hamzah; Harumi Veny; Miradatul Najwa Mohd Rodhi; Mahanim Sarif (ASEAN Journal of Chemical Engineering, 2021)
This paper presents the utilization of bamboo residue from the chopstick industry as modified carbon (AC) for supercapacitor application.  Bamboo activated carbon (BAC) was activated using Potassium hydroxide (KOH) and assisted with microwave ultrasonic (Mw-U) irradiation to enhance the properties of bamboo activated carbon (BAC). Different microwave (Mw) power intensities of 100 W, 300 W, and 500 W at 30 minutes of retention time have been applied on activation and the carbonization process was conducted at temperature 800°C. The BAC was analyzed for the morphology using a scanning electron microscope and proximate and ultimate analysis. Then BAC with the higher surface area was subjected to the electrochemical analysis to determine the electrochemical properties. The study indicated Mw-U irradiation improved the morphology of the BAC, eliminated the impurity of the sample, and gave higher carbon content of BAC. The findings show that lower Mw-U irradiation power provided a higher surface area of BAC. The surface area of 646.87 m2/g and total pore volume of 2.8x10-1 cm3/g was obtained with a power intensity of Mw-U activation at 100 W. While, electrochemical properties, the specific capacitance (Cs) of BAC was 77 Fg-1 at 25 mVs-1 in 1 mol/L KOH of electrolyte for cyclic voltammetry (CV) which indicates the ability of the prepared BAC to be used as an electrode in supercapacitor application. This study determined that Mw-U irradiation can improve the properties of the bamboo during chemical activation and formed BAC that consists of supercapacitor properties.